Enhanced recovery after surgery protocol optimizes results and cost of laparoscopic radical nephroureterectomy - Jiageng Shi; Siming Chen; Jiawei Nie; Kangping Xiong; Gang Wang; Kaiyu Qian; Hang Zheng; Xinghuan Wang (BMC Surgery)
Abstract Purpose To evaluate the efficacy of an enhanced recovery after surgery (ERAS) strategy for upper tract urothelial carcinoma (UTUC) patients undergoing laparoscopic radical nephroureterectomy (LRNU). Methods 90 patients who received LRNU at Zhongnan Hospital of Wuhan University between January 2018 and July 2022 were retrospectively analyzed, including 43 in the ERAS group and 47 in the pre-ERAS group. The clinical features, postoperative complications, length of hospital stay (LOS), and hospital expenditures of the two groups were compared via t-test, Mann-Whitney test, and Chi-square test. Results In comparison to the pre-ERAS group, the total and postoperative LOS were significantly shorter in the ERAS group [total LOS: 15.0 (13.0–20.0) vs. 21.0 (16.0–26.0), p < 0.001; postoperative LOS: 8.0 (7.0–9.0) vs. 11.0 (9.0–13.0), p < 0.001]. The ERAS group had lower hospitalization costs than that in the pre-ERAS group [56896.40 (48324.30-67498.01) vs. 64249.83 (55574.36-81581.82), p = 0.010]. Additionally, the ERAS group experienced a reduction in postoperative fever incidence (23.4% vs. 4.7%, p = 0.011). Conclusions In the realm of LRNU, ERAS protocols are safe and practical for minimizing the LOS while accelerating the rehabilitation of patients undergoing LRNU. This study offers insights for enhancing ERAS protocols for UTUC patients even further.